2011
DOI: 10.4093/dmj.2011.35.5.504
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Chronic Complications in Korean Patients with Type 2 Diabetes Mellitus Based on the Korean National Diabetes Program

Abstract: BackgroundThe Korean National Diabetes Program (KNDP) cohort study is performing an ongoing large-scale prospective multicenter investigation to discover the pathogenesis of type 2 diabetes in Korean patients. This study was performed to examine the prevalence of chronic complications in patients with type 2 diabetes among those registered in the KNDP cohort within the past 4 years.MethodsThis study was performed between June 2006 and September 2009 at 13 university hospitals and included 4,265 KNDP cohort par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 22 publications
1
63
0
3
Order By: Relevance
“…The prevalence of DR has ranged between 7.0% and 38.3% in other Korean studies. [24][25][26][27] In a previous investigation in a Korean outpatient type 2 DM cohort performed in 1995, 20% of patients had microalbuminuria and 14% had overt proteinuria. 28 In 2006, 30.3% of diabetic patients were found to have microalbuminuria in a Korean nationwide survey.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of DR has ranged between 7.0% and 38.3% in other Korean studies. [24][25][26][27] In a previous investigation in a Korean outpatient type 2 DM cohort performed in 1995, 20% of patients had microalbuminuria and 14% had overt proteinuria. 28 In 2006, 30.3% of diabetic patients were found to have microalbuminuria in a Korean nationwide survey.…”
Section: Discussionmentioning
confidence: 98%
“…In type 2 diabetes, the prevalence of CVD is 2- to 4-fold higher than in the general population [1-3]. Because of the clinical importance of CVD and the related morbidity and mortality in type 2 diabetes, predictable risk engines based on large epidemiologic studies have been suggested to identify the risk factors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the clinical importance of CVD and the related morbidity and mortality in type 2 diabetes, predictable risk engines based on large epidemiologic studies have been suggested to identify the risk factors [4,5]. Nevertheless, most of the previous studies were performed using only conventional risk factors (hypertension, lipid abnormalities, smoking, and obesity) for explaining the higher incidence of CVD in patients with type 2 diabetes [1-3]. Therefore, beyond the known modifiable risk factors, identification of another biomarker might be helpful for early detection and prediction of the future development of CVD in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a cross-sectional study using the database of patients with type 2 DM obtained from the KNDP, a prospective, large cohort study that began in 2005 [8].…”
Section: Study Populationmentioning
confidence: 99%